COSO ERM Framework as the Basis of Strategic Planning in Islamic Banking - Wahyuni, Rila Sanda; Novita, Novita (University of Merdeka Malang, 2021)
In digital era, every business entities must prepare a competitive strategy to compete with other competitors. Therefore, this study aims to provide management systems that can assist management in creating a competitive advantage. This study will describe the effect of Enterprise Risk Management (ERM) in strategic planning for Islamic banking use COSO ERM Framework approach. This study uses quantitative analysis method with purposive sampling technique on employees of Bank Syariah Mandiri (BSM) branch offices in DKI Jakarta. Descriptive analysis methods and verification analysis used to test hypotheses and structural models with the Smart Partial Least Square (PLS) program version 3.3.7. The results show that the ERM variable has a positive effect on strategy planning at Bank Syariah Mandiri (BSM). Strategic planning in BSM is 72.5% influenced by the risk management carried out by the company. In the strategic planning, management has made risk management report as a basis for analysis of the internal and external company.DOI: https://doi.org/10.26905/jkdp.v25i1.5123